Documentation strategies on agile software development projects. (1st January 2012) - Hoda, Rashina; Noble, James; Marshall, Stuart
Agile software development methods and their proponents suggest 'just enough' documentation on agile projects. However, for practitioners of these methods it remains unclear how much is 'just enough' documentation. Based on a grounded theory study of 58 agile practitioners from 23 different software organisations in New Zealand and India, we found several documentation strategies being used by agile teams to overcome various challenges they faced. These documentation strategies include documenting electronic back-ups of physical paper artefacts that are prone to damage and loss; documenting change decisions by customers to trace changes and avoid disagreements; documenting business terminology for more effective requirements elicitation; documenting the traditional way when collaborating with non-agile teams; and documenting positive customer feedback to demonstrate advantage of agile adoptions. These documentation strategies collectively help define 'just enough' documentation by describing the different forms and amounts of documentation agile teams engage in.